Juridical Review of Coal as an Object of Fiduciary Collateral in Banking Credit Agreements (Study of the Decision of Pt Anzawara Satria V. PT Bank Artha Graha Internasional TBK) - Ridho Gusti, Masangger Junio; Salam, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Mining activity is a capital-intensive industry that requires enormous cost. In supporting financing in mining activities, one of the sources is through a bank credit facility. With a series of mining activities that are quite complex, there is a high risk of financing from mining activities, one of which is the risk of non-performing loans. In anticipating these risks, banking institutions in practice have implemented the prudential principle through the implementation of 5C, one of which is guarantee (collateral). Based on Judicial Decision Number 714/ PDT /2016/ PT.DKI between PT Anzawara Satria against PT Bank Artha Graha Internasional, Tbk., PT Anzawara Satria as a mining company has provided guarantees in the form of coal supplies to PT Bank Artha Graha International Tbk. This research will review the material properties of coal as bank guarantees and analyse the position of coal as collateral based on Indonesian Mining Law. This research uses a normative juridical method with sources from secondary data, namely: (1) primary data materials in the form of relevant laws and regulations; (2) secondary data material, which includes books, journals, articles, or other related sources. This research resulted that, first, based on the nature of coal, coal may be guaranteed by fiduciary and pledge. Second, based on mining law in Indonesia, coal may be guaranteed with the condition that mining business actors are required to pay production fees (royalties) as a form of transfer of ownership rights from the state to business actors